2017
DOI: 10.1016/s2468-2667(16)30020-2
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death in people diagnosed with HIV in the era of highly active antiretroviral therapy compared with the general population: an analysis of a national observational cohort

Abstract: Public Health England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
269
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(293 citation statements)
references
References 22 publications
14
269
3
7
Order By: Relevance
“…As seen in British [24,25] and Swiss [26] HIV cohorts, we observed a steady decline in all-cause mortality among PLWHA over the past 20 years. As of December 31, 2018, 85.6% of persons diagnosed in the pre-highly active antiretroviral therapy era had died compared with 65.3%, 34.3%, and 12.7% in 1997-2006, 2007-2012, and 2013-2018, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…As seen in British [24,25] and Swiss [26] HIV cohorts, we observed a steady decline in all-cause mortality among PLWHA over the past 20 years. As of December 31, 2018, 85.6% of persons diagnosed in the pre-highly active antiretroviral therapy era had died compared with 65.3%, 34.3%, and 12.7% in 1997-2006, 2007-2012, and 2013-2018, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Monitoring the HIV continuum of care in relation to migrant populations is particularly challenging because of the lack of information (especially for undocumented migrants, who are the most vulnerable group and least likely to be in HIV care, receive treatment and achieve viral suppression ) and high levels of mobility. The absence of data is of concern because migrants account for a significant proportion of new HIV diagnoses in Europe, are most likely to be diagnosed late and to die sooner , and may be less likely to seek health care because of concerns about migration status .…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the Swiss HIV Cohort Study (SHCS) found that during the years 1988 to 2008, suicide rates decreased somewhat with the introduction of cART, but remained above the rate observed in the general population. A recent study in the UK also found that in the cART era, HIV‐related suicide rates were higher than in the general population .…”
Section: Introductionmentioning
confidence: 96%